(untitled) (Bodhi Path, 2025)
Human consciousness being, one of the greatest mysteries of this universe manifolds the very epicenter of the mind in certain ways through awareness of internal and external existence. Consciousness comprises of six categories: visual, auditory, olfactory, gustatory, tactile and mental consciousness in which the first five are sense consciousness. Each emerges depending on a physical sense faculty and the last is the mental consciousness (manovijñāna) [1]which arises depending on the mental sense faculty furthermore in Buddhist psychology, there is seventh consciousness and eighth consciousness namely the mind – consciousness (manas-vijñāna) and the storehouse consciousness (ālāyavijñāna). Hence, consciousness is something that occurs uninterruptedly throughout all of one’s worldly lifetime. It descends into the mother’s womb at the beginning of each life and departs at the end of one’s death and so on the process continues through a cycle of birth and rebirth, and ends with nirvana. Whereas subduing the thought that consciousness departs as one dies can be rationally subdued by the incorporation of a high level of meditation which enables one to achieve spiritual liberation by experiencing the fundamental nature of the mind which is known as Tukdam.